Penguatan dan Bimbingan Trend Fashion Islami Bagi Mahasiswi di Universitas Islam Negeri (UIN) Raden Mas Said Surakarta - Fatwa, Dian Islamiati; Zidatin Nurkumala, Emilda Triana (Jurnal Dedikasia : Jurnal Pengabdian Masyarakat, 2023)
Capitalism doesn't just impact women but also men. It has even conquered religion and commodified religious symbols. It can infiltrate religious symbols and transform them from within while offering the concept of "pious yet trendy" or 'worship yes, trendy yes.' Lifestyle and fashion have become inseparable parts of modern society. It's not just about the cover but the essence. This can be seen through the numerous trending models at the moment, leading many young people or teenagers to emulate their clothing styles. The purpose of this writing is to help us understand the difference between lifestyle and fashion in the past and today, as lifestyle and fashion have become integral parts of modern society. The research method used is library research. The research results show the existence of silent social preferences adopted by society, replacing old values.